2006
DOI: 10.1002/pbc.21063
|View full text |Cite
|
Sign up to set email alerts
|

Demographic correlates of body size changes in children undergoing treatment for acute lymphoblastic leukemia

Abstract: In our cohort of ALL patients, BMI was elevated at diagnosis (mean standardized BMI z-score = 0.22, standard deviation = 1.4) then increased and remained elevated for the entire duration of chemotherapy. Children who were 2-9 years of age at diagnosis began therapy with a substantially lower BMI and remained lower over the course of chemotherapy than patients aged 10-18 years at diagnosis. It will be important for future investigations to explore the biological and behavioral factors that may underlie such dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…First, we performed the analysis after excluding 7 studies 29,33,34,[36][37][38][39] for which the mean BMI z score or its SD was not explicitly reported or could not be calculated based on subgroup values (for mean BMI z score) or 95% CIs (for SD of BMI z score). We also repeated the analysis after excluding 7 longitudinal studies that did not report sample size of survivors at the follow-up evaluation, 8,12,29,33,34,36,38,42 for which we substituted it with the sample size reported at cancer diagnosis assuming loss to follow-up was random. In addition, we performed a "leave-one-out meta-analysis" to evaluate the impact of individual studies on the summary estimates.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, we performed the analysis after excluding 7 studies 29,33,34,[36][37][38][39] for which the mean BMI z score or its SD was not explicitly reported or could not be calculated based on subgroup values (for mean BMI z score) or 95% CIs (for SD of BMI z score). We also repeated the analysis after excluding 7 longitudinal studies that did not report sample size of survivors at the follow-up evaluation, 8,12,29,33,34,36,38,42 for which we substituted it with the sample size reported at cancer diagnosis assuming loss to follow-up was random. In addition, we performed a "leave-one-out meta-analysis" to evaluate the impact of individual studies on the summary estimates.…”
Section: Discussionmentioning
confidence: 99%
“…These survivors had completed treatment within 10 years at the time of study evaluation. 8,12,13,16,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Only 2 studies 14,40 examined BMI z score assessed $10 years after the completion of treatment (ie, off treatment $10 years). Because neither study reported SD/SE of the BMI z score, the meta-analysis did not include survivors who were off treatment beyond 10 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations